Metaphor and the 'Emergent Property' Problem: A Relevance-Theoretic Approach - Deirdre Wilson; Robyn Carston (Baltic International Yearbook of Cognition, Logic and Communication, 2007)
The interpretation of metaphorical utterances often results in the attribution of emergent properties; these are properties which are neither standardly associated with the individual constituents of the utterance in isolation nor derivable by standard rules of semantic composition. For example, an utterance of ‘Robert is a bulldozer’ may be understood as attributing to Robert such properties as single-mindedness, insistence on having things done in his way, and insensitivity to the opinions/feelings of others, although none of these is included in the encyclopaedic information associated with bulldozers (earth-clearing machines). An adequate pragmatic account of metaphor interpretation must provide an explanation of the processes through which emergent properties are derived. In this paper, we attempt to develop an explicit account of the derivation process couched within the framework of relevance theory. The key features of our account are: (a) metaphorical language use is taken to lie on a continuum with other cases of loose use, including hyperbole; (b) metaphor interpretation is a wholly inferential process, which does not require associative mappings from one domain (e.g. machines) to another (e.g. human beings); (c) the derivation of emergent properties involves no special interpretive mechanisms not required for the interpretation of ordinary, literal utterances.
Keywords: linguistics; philosophy